An Empirical Assessment of the Determinants of Financial Performance of Commercial Banks in Afghanistan - Khalilullah; Nawaz, Fahim; Zeb, Ali; Jehan, Noor (iRASD Journal of Economics, 2023)
The primary aim of the current paper is to gauge the impact of bank-specific/internal, and macroeconomic/external factors on the financial performance of Afghanistan’s commercial banks. For this purpose, data from 16 commercial banks was employed ranging from a time series from 2007 – 2016. The study is limited by the availability of recent data. This study employs the random effects model. This model is chosen using the Hausman test, which rendered random effects as the optimal technique for this study. Banking performance is gauged using return on assets (ROA) and net interest margin (NIM) assumed to be the functions of salient internal and external factors. This paper finds that capital adequacy and asset quality positively influence NIM, while inflation and GDP exert negative impacts on it. Likewise, ROA is positively influenced by capital adequacy, asset quality, liquidity management, & GDP. Conversely, management efficiency negatively affects ROA. These finds indicate that banks can greatly enhance their profits by improving management and decreasing the credit/asset ratio. This indicates a strong influence of internal factors on Afghanistan’s commercial banks.